Causes of Employee Turnover: A Case Study of an Indian Company - Velamati, Anusha (2009)
Human assets, which refer to the unique capabilities and skills that an individual possesses, are the most valuable form of assets in an organization. The value of such assets can increase as opposed to other kinds of assets. The loss of these human assets could cause a deep loss to the organization. To avoid such a kind of a loss to the organization, appropriate measures such as knowing what causes employees to leave organization should be studied. This study thus aims to highlight some of the reasons that could cause employees to leave their respective companies. The motivation for this study has been due to the alarming rates of employee turnover being experienced in a lot of companies. A vast amount of literature has been generated on employee turnover in which some of the causes, measurement of employee turnover, models of employee turnover and the effects will be studied. A qualitative approach has been used for this research. Semi-structured interviews with 15 former employees of a company based in India were conducted to find out what made these employees leave the company and why it was of significance to them. A model that was reviewed in the literature section has been tested to find out whether the results found in this research and the results found by the researcher are similar or whether they vary. The model helped in being able to predict turnover, which is of significance to managers as they could take necessary steps to avoid the turnover of their employees.